Meiotic crossovers characterized by haplotype-specific chromosome painting in maize - Lívia do Vale Martins (Nature Portfolio, 2019)
Meiotic crossovers (COs) are essential for proper chromosome segregation and generating novel combinations of alleles. Here, the authors develop haplotype-specific oligos on maize chromosome 10 for fluorescence in situ hybridization and analyze CO patterns in an intermated recombinant population derived from B73 and Mo17.